Geological repositories: scientific priorities and potential high-technology transfer from the space and physics sectors. (2nd January 2018) - Direito, Susana O. L.; Clark, Samantha; Cousins, Claire; Fujita, Yoshiko; Gluyas, Jon; Harley, Simon; Holmes, Richard J.; Hutchinson, Ian B.; Kudryavtsev, Vitaly A.; Lloyd, Jon; Main, Ian G.; Naylor, Mark; et al.
Abstract: The use of underground geological repositories, such as in radioactive waste disposal (RWD) and in carbon capture (widely known as Carbon Capture and Storage; CCS), constitutes a key environmental priority for the 21 st century. Based on the identification of key scientific questions relating to the geophysics, geochemistry and geobiology of geodisposal of wastes, this paper describes the possibility of technology transfer from high-technology areas of the space exploration sector, including astrobiology, planetary sciences, astronomy, and also particle and nuclear physics, into geodisposal. Synergies exist between high technology used in the space sector and in the characterization of underground environments such as repositories, because of common objectives with respect to instrument miniaturization, low power requirements, durability under extreme conditions (in temperature and mechanical loads) and operation in remote or otherwise difficult to access environments.